Reporting drying temperature and humidity may give more standardised results - Başaran, Betül; Tolu, Sena (Churchill Livingstone, 2021)
We read with interest the recent article about the simulation studyby Taylor et al.1that showed a high incidence of chlorhexidine trans-fer from skin to gloves, and also from gloves to another surface.Although the simulation study was well designed to demonstrate theseprimary and secondary aims, the actual drying process depends onboth the temperature of volunteers and the environment, and alsothe humidity of the environment
Keywords: Antisepsis; Chlorhexidine Gluconate; Contamination